Drug binding and drug-drug interaction considerations in individuals with obesity before and after bariatric surgery: A retrospective cross-sectional study - Emerita Quintina de Andrade Moura; Carolina Dumke de Siqueira; Ana Carolina Martins; Bruno Fonseca Nunes; Ana Carolina Rabello de Moraes; Fabíola Branco Filippin-Monteiro (Elsevier, 2023)
Obesity impacts pharmacokinetic and pharmacodynamic parameters, changing the drug-binding state via plasma proteins, which is critical for drug effectiveness and toxicity. Albumin and α1-acid glycoprotein (AAG) are the two main proteins accountable for drug binding in humans. Previous studies have shown higher values of AAG in individuals with obesity, but the interference of AAG in the pharmacokinetics of drugs remains unclear. We, therefore, aimed to analyze the pharmacotherapeutic profile and interfering factors in patients undergoing bariatric surgery in the pre-operative period and after 12 months. A retrospective cross-sectional study design was conducted and serum AAG was determined, and potential drug-drug interactions were monitored in patients with severe obesity who underwent bariatric surgery. The drug classes most used were antidepressants, cardiovascular agents, and lipid-modifying agents, with a decrease in use after 12 months of surgery. Before surgery, it was found that more than half of the patients had at least one drug interaction in their therapeutic regimen. Of these, most were classified as moderate. After surgery, a decrease in drug interaction was observed. Serum AAG showed a significant reduction after 12 months, which can influence the free fraction of drugs with a high-affinity rate and how they impact therapeutic efficacy.